2018
DOI: 10.1111/psyg.12364
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between caregiver burden and caregiver pulse rate measured by using a wristwatch‐type pulsimeter with accelerometer in home‐based family caregivers for persons with dementia: Pilot study

Abstract: The relationship between caregiver burden and caregiver pulse rate measured by using a wristwatch-type pulsimeter with accelerometer in home-based family caregivers for persons with dementia: Pilot study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
6
0
3
Order By: Relevance
“…26 Home-based care is becoming increasingly critical in Japan; therefore, it is meaningful to determine how to reduce objective care burden among FCs. 27 Our results indicated that reduced objective total sleep time (as measured by the ActiGraph) is significantly associated with FCs' care burden severity. Additionally, care burden severity and a shorter total sleep time might represent more severe care burden among CRs.…”
Section: Discussionmentioning
confidence: 60%
“…26 Home-based care is becoming increasingly critical in Japan; therefore, it is meaningful to determine how to reduce objective care burden among FCs. 27 Our results indicated that reduced objective total sleep time (as measured by the ActiGraph) is significantly associated with FCs' care burden severity. Additionally, care burden severity and a shorter total sleep time might represent more severe care burden among CRs.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies of caregivers to lung cancer patients demonstrated that the comprehensive health enhancement support system can improve a caregiver's understanding, carers' appraisal, and problem-focused coping strategies [4,5]. Furthermore, the possibility of maintaining the health of carers using wearable devices has also been suggested [6], and such support using devices is considered useful for caregivers of persons with cancer.…”
Section: Dear Editormentioning
confidence: 99%
“…This systematic review indicates, as it only includes one article, that research about caregiver burden using new technology for informal caregivers of people with dementia is lacking. However, recent studies have reported the usefulness of wearable devices for caregivers of people with dementia and other areas . Another study examined sleep using watch‐type actigraphs and biomarkers of objective measurements for Alzheimer's caregivers .…”
mentioning
confidence: 99%